Preliminary study of antibacterial properties in Mapania - Nur Syauqina Syasya, binti Mohd Yusoff (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The aim of this research was to study the antibacterial properties from the leaves and rhizomes of five different Mapania species (M. cuspidata var petiolata, M. meditensis, M. lorea, M. walichii and M. hispida). Ten group flavonoids compound were identified which are 5-deoxyisoflavones, isoflavones, chalcone, flavanones, anthocyanins, flavone glycoside, flavones, flavonols, glycosylflavones and aurones by using 2-D chromatography paper. Antibacterial activities of ethanolic flavonoids extract from leaves and rhizomes of each species were carried out against E. coli 0157:H7 and B. cereus ATTC 33019. In disc diffusion test methods, it was found that M. cuspidata var petiolata has showed high inhibition zone (1.4 cm) among all the species with the MIC of 0.125 mg/ml in both E. coli 0157:H7 and B. cereus ATTC 33019. The leaves have the highly inhibition zone than the rhizomes in both E.coli and B. cereus.